Ainda acerca das reflexões sobre a situação teórica das ciências sociais: uma crítica ao turismo enquanto fenômeno - Tadioto, Mateus Vitor (My University, 2022)
This thesis has as its starting point a reflection on the statement "the human being moves", associated with tourism. In face of this reflection, it became necessary to organize an overview of theoretical production in the Tourism epistemology. This panorama allowed us to observe the limits and disputes in the theoretical field, expressed in the multiplicity of epistemological approaches, and exposing the conditions of the intellectual work/labor division. This analysis highlighted the recurrence of the tourism binomial/phenomenon implied in an idealistic approach to knowledge production. The reflection incited an internal criticism through the methodological analytical theoretical device of materialistic french Discourse Analysis. For this analysis, basic sections were selected which reformulations required the articulation of the concept of interdiscourse, and its modes of functioning, pre-constructed and discourse-transverse. These concepts open the possibility to discuss the use of the notion of the phenomenon, as a rhetorical resource, and tourism as a practice of transformation of destinations (the place) into destinations (the tourist imaginary about the place). This composition can defocus the tourist subject and places a practice that exposes the contradictions in social formation as the engine of the process. [resumo fornecido pelo autor]
Esta tese tem como ponto de partida uma reflexão sobre o enunciado "o ser humano se desloca", associado ao turismo. Frente a essa reflexão, fez-se necessária a organização de um panorama acerca da produção teórica em epistemologia do Turismo. Tal panorama possibilitou observar os limites e as disputas pelo campo teórico, expressos na multiplicidade das abordagens epistemológicas, expondo também as condições da divisão do trabalho intelectual. Essa análise pôs em evidência a recorrência do binômio turismo/fenômeno implicada em uma abordagem idealista de produção de conhecimento. A reflexão incitou uma crítica interna através do dispositivo teórico analítico metodológico da Análise de Discurso francesa materialista. Para essa análise foram selecionadas sequências de base cujas reformulações exigiram a articulação do conceito de interdiscurso, seus modos de funcionamento - pré-construído e discurso-transverso. Esses conceitos abrem uma possibilidade para discutir o uso da noção de fenômeno, enquanto recurso retórico e o turismo enquanto prática de transformação de destinos (o lugar) em destinações (o imaginário turístico sobre o lugar). Essa elaboração descentra o sujeito turista e coloca como motor do processo uma prática que expõem contradições na formação social. [resumo fornecido pelo autor]
Keywords: Turismo; Teoria do conhecimento; Fenomenologia; Turismo - Prática; Análise do discurso; Tourism; Knowledge, Theory of; Phenomenology; Tourism - Practice; Discourse analysis